Optimasi metode ekstraksi air umbi talas Jepang (Colocasia esculenta (L) Schott)): analisis aktivitas antioksidan, kandungan flavonoid, dan kadar luteolin - Desmiaty, Yesi; Sandhiutami, Ni Made Dwi; Okta , Fauzia Noprima; Marvel, Nadya Sekar; Sumiyati , Yati (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Japanese taro (Colocasia esculenta (L) Schott)) is one of the edible plants that contain phytochemicals such as flavonoids, phenolics, triterpenoids, tannins, and vitamin C which are beneficial to the health of the human body. The compound is also known to have antioxidant activity. Proper extraction can produce quality extracts. This study aims to optimize the extraction method on Japanese taro tubers. Taro tuber was extracted using water with three different temperatures (room temperature, 40℃, and 60℃). The ABTS (2,2'-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) method was used to determine the antioxidant activity of the aqueous extract, in addition to determining the total flavonoid content by colorimetric test, and also analyzing the luteolin content by Thin Layer Chromatography (TLC) Densitometry. The total flavonoid content of Taro extracts at room temperature (TERT), 40℃ (TE 40), and 60℃ (TE 60) were 13.97±3.52 mg QE/gr extract; 7.99±2.10 mg QE/gr extract; and 5.98±0.49 mg QE/gr extract, respectively. Luteolin content of TERT, TE40, and TE60 were 0.27%±0.08; 0.25%±0.06; and 0.31%±0.05, respectively. Antioxidant IC50 values of TERT, TE40, and TE60 were 120.32, 137.03, and 159.37 µg/mL, respectively. The study shows that the greater the temperature in the extraction process, the less flavonoid and antioxidant compounds content. While there is a slight difference in determining luteolin levels, optimum luteolin content is obtained at 60°C for 6 hours.